2018
DOI: 10.1155/2018/7501985
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Macrophages by Oligomeric Proteins of Different Size and Origin

Abstract: Activation of macrophages is one of the key processes in generating the immune response against pathogens or misfolded/aggregated otherwise unharmful host's proteins. Antigens and their immune complexes (IC) may shape macrophage phenotype in various directions. Data on the impact of protein structure during inflammation are evident; however, some separate steps of this process involving changes in macrophage phenotype are not fully understood. Our aim was to investigate the phenotype of macrophages after activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
(79 reference statements)
1
6
0
Order By: Relevance
“…Together, these experiments conclusively demonstrated that SARS-CoV-2 S protein modulates the aggregation state of LPS, analogously to the effects reported for other LPS-binding proteins such as LBP (Kitchens and Thompson, 2005;Ryu et al, 2017). Further, previous reports indicate that LPS and protein aggregates can be proinflammatory (Mueller et al, 2004;Dalgediene et al, 2018). Moreover, LBP can form aggregates with LPS, particularly at a high LPS/LBP ratio (Kitchens and Thompson, 2005), providing additional links to the present findings with SARS-CoV-2 S protein.…”
Section: Discussionsupporting
confidence: 88%
“…Together, these experiments conclusively demonstrated that SARS-CoV-2 S protein modulates the aggregation state of LPS, analogously to the effects reported for other LPS-binding proteins such as LBP (Kitchens and Thompson, 2005;Ryu et al, 2017). Further, previous reports indicate that LPS and protein aggregates can be proinflammatory (Mueller et al, 2004;Dalgediene et al, 2018). Moreover, LBP can form aggregates with LPS, particularly at a high LPS/LBP ratio (Kitchens and Thompson, 2005), providing additional links to the present findings with SARS-CoV-2 S protein.…”
Section: Discussionsupporting
confidence: 88%
“…Notably, such aggregates were also induced by lipid A, the core of the LPS molecule, common for endotoxin producing bacteria. Previous reports indicate that both LPS and protein aggregates can be proinflammatory (27,28), and moreover, the well-known LPS-binding protein (LBP) forms proinflammatory aggregates with LPS particularly at a high LPS/LBP ratio (29).…”
Section: Discussionmentioning
confidence: 99%
“…These results are supported by a study using primary macrophages, demonstrating how immune response is dependent on the origin, size, and shape of proteins. In fact, by comparing to Aβ fibrils, AβOs induce in a greater extent the expression of M1‐related markers CD86, IL‐23, and TNF‐α (Dalgediene, Luciunaite, & Zvirbliene, 2018). Results in microglial culture may explain the recent failure of several Aβ immunotherapies.…”
Section: Glial Cellsmentioning
confidence: 99%